(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Chalcones are the main building blocks for flavonoids and isoflavonoids biosynthesis. Chalcones are made up of a three-carbon, α,β -unsaturated carbonyl system. Chalcones are the products of aromatic aldehyde condensation with acetophenones in the presence of a catalyst. They are useful in the synthesis of pyrazoline, isoxazole, and a variety of heterocyclic compounds because they go through a variety of chemical reactions. For the synthesis of these compounds, a variety of methods and schemes have been reported. Aldol condensation and Claisen-Schmidt condensation are still at the top of the list. Other notable techniques , Chalcones are active lead compounds that can be used to find new medications in medicinal chemistry. This section will explain characteristics and biosynthesis